THE EFFECTIVENESS OF REALISTIC MATHEMATICS EDUCATION (RME) APPROACH IN MATHEMATICS LEARNING OF STUDENTS IN MTs NEGERI GODEAN SLEMAN - Fitria Fitria; Edi Prajitno (Universitas Ahmad Dahlan, 2017)
Teacher-centered learning often makes students feel bored and not interested in participating in learning mathematics. This causes students to be less active in learning activities so that students become less familiar with the material described by teachers and resulted in low learning outcomes of mathematical learning. This study aims to determine whereas more effective learning between mathematics learning using the Realistic Mathematics Education (RME) approach with mathematics learning using a traditional approach to mathematics learning outcomes of students. The population in this study is the seventh-grade students of MTs Negeri Godean Sleman in the academic year 2015/2016 which consists of 4 classes. The sampling technique using a purposive sampling technique (sampling technique with certain considerations) to the class that obtained class VII B as an experimental class and class VII A as a control class. The data was collected using the test method. Instrument testing used validity, reliability, and difficulty level. The data analysis technique used analysis prerequisites of normality test, homogeneity test, and hypothesis testing. The result showed that 1) there is a different learning outcome between learning mathematics using the Realistic Mathematics Education (RME) approach with learning mathematics using a traditional approach. It’s based on two-tailed t-test obtained and with a significance level of 5% and the degrees of freedom, respectively and , which meanings , and than is rejected and accepted. 2) Learning mathematics using the Realistic Mathematics Education (RME) approach is more effective than learning mathematics using the traditional approach through mathematics learning outcomes on seventh-grade students of MTs Negeri Godean Sleman in the academic year of 2015/2016. It is based on the one tiled t-test obtained and with a significance level of 5% and the degrees of freedom, respectively and which meanings , and than is rejected and accepted.